Anticholinergic burden and fractures: a protocol for a methodological systematic review and meta-analysis - Oliver Riedel; Francesco Barone-Adesi; Jonas Reinold; Wiebke Schäfer; Lara Christianson; Federica Edith Pisa (BMJ Open)
Introduction Medications with anticholinergic activity are used in the treatment of many diseases common in old age, including depression, psychosis, Parkinson’s disease, allergies, pain and urinary incontinence. A high anticholinergic burden (ACB) is considered a major risk factor for fractures in older adults but recent studies reported inconsistent results. These inconsistencies may partly be due to differences in methodological aspects. However, no systematic review so far has addressed this association and considered study methods. Thus, we aim to conduct a systematic review and meta-analysis of observational studies addressing the association of ACB with fractures and to provide a methodological appraisal of the included studies.Methods and analysis We will search MEDLINE, EMBASE, the Science Citation Index, CENTRAL and grey literature using a strategy that combines the terms anticholinergic and fractures. We will hand search reference lists of articles. Two reviewers will independently screen all identified abstracts for eligibility and evaluate the risk of bias of the included studies using the Newcastle-Ottawa Quality Assessment Scale and RTI item bank. Discrepancies will be resolved by consensus or consultation with a third researcher. We will conduct a meta-analysis, either for the overall population or for specific and more homogeneous subgroups, if the number of studies retrieved and their heterogeneity allows it.Ethics and dissemination No ethics approval will be sought, as no original data will be collected for this review. Findings will be disseminated through peer-reviewed publication and conference presentations.PROSPERO registration number CRD42018116737.